Designing & Development of a Whisker-Sensor-Based Robot - Hamed F.Alsalhin Saleh; Fathalla I. Solman; Zead Hamad Abdulkarim; Salem M Arhouma Elgatani (Libyan Journal of Medical and Applied Sciences, 2025)
Rats use their whiskers as tactile sensors to explore and understand their surroundings. One of the key behaviors observed in rodents is "active whisking", where they continuously move their whiskers back and forth to gather sensory information. This enables them to detect various object features such as texture, size, shape, and distance. In this study, soft resistive sensors are embedded into artificial whisker follicles, offering a simple, robust, and effective method for detecting environmental changes. The main objective of this research is to design and simulate a small robotic device capable of navigating through a maze. The robot uses the whisker-inspired sensors to detect and respond to obstacles. Upon encountering an obstacle, it reverses direction to its previous reference point before continuing along an alternate path. The robot starts at a designated point (e.g., Point A) and autonomously finds its way to a target location (Point B), choosing among different possible routes. Key design considerations include the control unit, wheel configuration, baseline diameter, sensing circuit, and stepper motor integration. The robot’s circuit was simulated using the PROTEUS design tool, while hardware implementation was carried out using MPLAB software and the ICD3 programming device.